2012
DOI: 10.1177/0892705712443247
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the tribological abrasive wear behavior of woven composite materials using the planning design experimentation approach

Abstract: This article addresses the experimental characterization of the abrasive wear of two woven fabric carbon fiber and glass fiber composite materials, taking into account the effect of moisture absorption. The composite materials were tested to three level loadings and two sliding speeds. The abrasive used was dry sand of size 0.6 mm, and the time of wear testing was 10 min. In order to study the effects of moisture on wear behavior, another series of samples was introduced into the tank of water during a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A comparatively low specific wear rate was seen for a 0° fiber orientation, while fibers at 90° showed almost three times higher wear rate. Zenasni et al 10 characterized the abrasive wear behaviors of two woven fabric carbon fiber and glass fiber composite materials, taking moisture absorption into account. The results showed that, as speed and load increased, matter loss also increased.…”
Section: Introductionmentioning
confidence: 99%
“…A comparatively low specific wear rate was seen for a 0° fiber orientation, while fibers at 90° showed almost three times higher wear rate. Zenasni et al 10 characterized the abrasive wear behaviors of two woven fabric carbon fiber and glass fiber composite materials, taking moisture absorption into account. The results showed that, as speed and load increased, matter loss also increased.…”
Section: Introductionmentioning
confidence: 99%